Arecibo PALFA survey and Einstein@Home: Binary pulsar discovery by volunteer computing - Knispel, B.; Lazarus, P.; Allen, B.; Anderson, D.; Aulbert, C.; Bhat, Ramesh; Bock, O.; Bogdanov, S.; Brazier, A.; Camilo, F.; Chatterjee, S.; Cordes, J.; et al. (Institute of Physics Publishing, 2011)
We report the discovery of the 20.7ms binary pulsar J1952+2630, made using the distributed computing project Einstein@Home in Pulsar ALFA survey observations with the Arecibo telescope. Follow-up observations with the Arecibo telescope confirm the binary nature of the system. We obtain a circular orbital solution with an orbital period of 9.4hr, a projected orbital radius of 2.8lt-s, and a mass function of f = 0.15 M ? by analysis of spin period measurements. No evidence of orbital eccentricity is apparent; we set a 2s upper limit e ? 1.7 × 10 -3 . The orbital parameters suggest a massive white dwarf companion with a minimum mass of 0.95 M ? , assuming a pulsar mass of 1.4 M ? . Most likely, this pulsar belongs to the rare class of intermediate-mass binary pulsars. Future timing observations will aim to determine the parameters of this system further, measure relativistic effects, and elucidate the nature of the companion star. © 2011. The American Astronomical Society. All rights reserved.